IMPLEMENTASI PEMBELAJARAN PKN BERBASIS INKLUSI DI HOMESCHOOLING - Ahmad Nasir Ari Bowo (Academy of Education Journal, 2016)
This study aims to describe the implementation of inclusive civics learning in homeschooling in Yogyakarta. This research method uses a qualitative approach. The results showed that in the homeschooling of Anak Pelangi Yogyakarta, in planning and developing inclusive learning in accordance with student characteristics. At the beginning of entry or registration, prospective students first do a fingerprint and psychological test. It is intended to get conclusions about the talents, interests, and potential of children, making it easier for teachers to develop children's potential according to their needs. Academic and psychological fields will provide test results to teachers that are used as recommendations and references for handling and teaching methods that are appropriate for students, so teachers can develop curricula in accordance with student characteristics. The implementation of learning in Homeschooling is shorter than formal schools in general. With the number of face-to-face and shorter duration, the teacher can deliver materials according to the abilities of each student. It can be seen that, the application of PPKn Yogyakarta Homeschooling Inclusion learning includes: (a) when the test enters prospective new students, they conduct a fingerprint test, and a psychological test, (b) the results of the fingerprint test and a psychological test are used to determine the characteristics, potential, background, of students, (c) the teacher applies an SBC curriculum that is developed according to the student's circumstances.